THE RIGHT TO ONLINE DATA PROTECTION OF CHILDREN: EXAMINING THE ADEQUACY OF THE LEGAL FRAMEWORKS TO COMBAT CHILD ONLINE DATA BREACHES IN NIGERIA - Iyoha-Osagie, Thummim; George, Orji Ikechukwu (ABUAD Private and Business Law Journal, 2019)
With the rise of digital technology and massive migration to the internet for daily activities, personal data of children is being breached on a large scale by schools, government, online platforms and even parents. It has been estimated that approximately one in three users of the Internet worldwide are under the age of eighteen. In addition to being increasingly active online, children also continue to depend on the Internet for a variety of uses such as play, communication and education. This implies that data belonging to children are frequently being collected through the use of gadgets, applications, and websites, and are sometimes sold or used for criminal activities. Several guidelines regarding children's online data protection have emerged globally such as the United States’ Children's Online Privacy Protection Rule ("COPPA"), United Kingdom’s ICO Children's Code (or Age Appropriate Design Code), and the General Data Protection Regulation (GDPR). However, there was no adequate provision for the protection of children’s data in Nigeria until the enactment of the Nigeria Data Protection Act which is a step in the right direction, but is not without its flaws. This paper seeks to determine the adequacy of the legal frameworks generally in Nigeria to deal with child data breaches. It takes a comparative approach by analysing several legal frameworks in other jurisdictions, and proffers recommendations including amendment of legislations, online safety measures and awareness, privacy and data protection by design approaches for companies and adequate parental control measures.